Graphitic Carbon Nitride as a Distinct Solid Stabilizer for Emulsion Polymerization. Issue 9 (17th January 2018) - Cao, Qian; Cui, Qianling; Yang, Yu; Xu, Jingsan; Han, Chenhui; Li, Lidong
Abstract: g‐C3 N4 has been found to be highly functional in many fields, such as photocatalysis, electrocatalysis, and chemical analysis. Pickering emulsion polymerization is a fascinating strategy to fabricate a range of nanomaterials, in which the emulsion is stabilized by solid particles, rather than molecular surfactants. Herein, we demonstrate that g‐C3 N4 can act as a remarkable stabilizer for Pickering emulsion polymerization. Contrary to normal Pickering systems, monodisperse polystyrene microspheres with tunable size, surface charge, and morphology were achieved using this approach. Importantly, the g‐C3 N4 hybridized latex is highly processable and has exhibited multiple functions: manufacture of photonic crystals via self‐organization, stabilizing Pickering emulsion owing to proper wettability, and acting as bioimaging agents with enriched fluorescent colors. Considering the easy synthesis and low cost of g‐C3 N4, our approach has a high potential for scale‐up synthesis and practical translation. Abstract : Small wonder : Graphitic carbon nitride (g‐C3 N4 ) was used as a Pickering‐type stabilizer for emulsion polymerization. Monodisperse polystyrene microspheres with tunable size, surface charge, and morphologies are produced, demonstrating remarkable processability and versatility (see scheme).